2017
DOI: 10.1002/sctm.17-0133
|View full text |Cite|
|
Sign up to set email alerts
|

Inferior In Vivo Osteogenesis and Superior Angiogeneis of Human Adipose-Derived Stem Cells Compared with Bone Marrow-Derived Stem Cells Cultured in Xeno-Free Conditions

Abstract: The possibility of using adipose tissue‐derived stromal cells (ATSC) as alternatives to bone marrow‐derived stromal cells (BMSC) for bone repair has garnered interest due to the accessibility, high cell yield, and rapid in vitro expansion of ATSC. For clinical relevance, their bone forming potential in comparison to BMSC must be proven. Distinct differences between ATSC and BMSC have been observed in vitro and comparison of osteogenic potential in vivo is not clear to date. The aim of the current study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 75 publications
4
67
0
4
Order By: Relevance
“…Similar to what has been reported in regard to the effectiveness of MSCs, with some tissue sources preferable for certain indications (e.g., umbilical cord MSCs for immunomodulatory tasks [ 33 ] and BMSCs for bone regeneration [ 2 ] ), the tissue of origin also impacts the effectiveness of the MSC secretome. First, there is a significant difference in the levels of soluble factors and EVs secreted by MSCs according to their tissue of origin [ 124,242 ] and MSCs secrete EVs enriched in distinct miRNA and tRNA species [ 243 ] and proteins [ 242 ] according to their tissue of origin.…”
Section: Future Challenges For the Clinical Translation Of Msc Secretmentioning
confidence: 73%
See 1 more Smart Citation
“…Similar to what has been reported in regard to the effectiveness of MSCs, with some tissue sources preferable for certain indications (e.g., umbilical cord MSCs for immunomodulatory tasks [ 33 ] and BMSCs for bone regeneration [ 2 ] ), the tissue of origin also impacts the effectiveness of the MSC secretome. First, there is a significant difference in the levels of soluble factors and EVs secreted by MSCs according to their tissue of origin [ 124,242 ] and MSCs secrete EVs enriched in distinct miRNA and tRNA species [ 243 ] and proteins [ 242 ] according to their tissue of origin.…”
Section: Future Challenges For the Clinical Translation Of Msc Secretmentioning
confidence: 73%
“…Mesenchymal stem/stromal cells (MSCs) are major cell candidates in regenerative medicine. MSCs can be isolated from diverse tissues in the body including the bone marrow, [ 1 ] adipose tissue, [ 2 ] umbilical cord, [ 3,4 ] placenta, [ 5 ] and dental pulp [ 6 ] ( Figure ). Some evidence indicates that MSCs in these tissues have a perivascular origin.…”
Section: Introductionmentioning
confidence: 99%
“…AT‐MSCs also differ in their differentiation potential when compared with BM‐MSCs. AT‐MSCs were able to differentiate towards the osteogenic lineage but not to the same extent as BM‐MSCs (Brennan et al, ; Im et al, ). However, in another study, there was no significant difference in the osteogenic potential of MSCs derived from BM and AT (De Ugarte et al, ).…”
Section: Adult Mscsmentioning
confidence: 99%
“…As previously discussed, abdominal adipose tissue represents a promising alternative to iliac bone marrow, since; (a) it is relatively less invasive to harvest, and (b) the average yield of MSC‐like cells are reportedly greater compared to bone marrow (Bajek et al., ; Qadan et al., ). However, previous studies have suggested a lower intrinsic osteogenic potential of ASCs versus BMSCs in vitro and in vivo (Brennan et al., ; Liao & Chen, ). Moreover, the in vivo bone‐forming potential of ASCs has been demonstrated only when pre‐cultured in the presence of additional osteogenic stimulating factors (Scherberich et al., ).…”
Section: Discussionmentioning
confidence: 92%